C-myc contributes to the release of Müller cells-derived proinflammatory cytokines by regulating lncRNA MIAT/XNIP pathway. (September 2019) - Zhang, Jiayu; Chen, Chengwei; Wu, Liang; Wang, Qiang; Chen, Jiawei; Zhang, Sifang; Chen, Zhenguo
Abstract: Müller cells-derived proinflammatory cytokines exert important roles in the development of DR, while the molecular mechanisms of its release were not fully elucidated. Present study aims to investigate the mechanism underlying the regulation of c-myc on the release of Müller Cells-derived proinflammatory cytokines. Streptozotocin was utilized to induce diabetes mellitus (DM) rat and glucose was used to stimulate Müller cells. The interaction between c-myc, lncRNA MIAT and TXNIP was determined by the luciferase reporter, CHIP, RNA pull-down, RIP and ubiquitylation assays. Increased c-myc protein level and concentrations of IL-1β, TNF-α and IL-6 were found in DM rats and high glucose stimulated Müller cells. After glucose stimulation, c-myc promoted the releases of IL-1β, TNF-α and IL-6. The up-regulation of MIAT under glucose treatment was mediated by c-myc binding to its promoter. MIAT interacted with TXNIP and increased TXNIP protein level by inhibiting its ubiquitination degradation. C-myc regulated TXNIP expression through MIAT in glucose induced Müller cells. Under glucose treatment, c-myc facilitated the release of Müller cells-derived IL-1β, TNF-α and IL-6 by regulating MIAT/TXNIP pathway. The in vivo study further indicated that c-myc knockdown attenuated DR progression in vivo. Our results suggested a mechanism by which c-myc facilitates the release of Müller Cells-derived proinflammatory cytokines by regulating MIAT/TXNIP pathway.